2001
DOI: 10.1001/jama.286.15.1857
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide Resistance Among Invasive <EMPH TYPE="ITAL">Streptococcus pneumoniae</EMPH> Isolates

Abstract: In the setting of increasing macrolide use, pneumococcal resistance has become common. Most resistant strains have MICs in the range in which treatment failures have been reported. Further study and surveillance are critical to understanding the clinical implications of our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
176
3
7

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(198 citation statements)
references
References 32 publications
12
176
3
7
Order By: Relevance
“…Permanecem relativamente baixas as cifras para a eritromicina (11,3%) e clindamicina (11,3%), comparáveis com as relatadas em outros estudos nacionais: para eritromicina, valores de 3,8 27 , 5,5 13-15 , 5,7 28 e 6,2% 24 e para clindamicina, valores de 2,9 28 e 3,1% 27 . O fato de 16 cepas resistentes à eritromicina serem também resistentes à clindamicina sugere a manifestação do fenótipo MLS B , caracterizado pela resistência constitutiva aos macrolídeos, lincosaminas e estreptogramina B 29,30 . Não houve resistência in vitro ao cloranfenicol, ofloxacina, rifampicina ou vancomicina.…”
Section: Discussionunclassified
“…Permanecem relativamente baixas as cifras para a eritromicina (11,3%) e clindamicina (11,3%), comparáveis com as relatadas em outros estudos nacionais: para eritromicina, valores de 3,8 27 , 5,5 13-15 , 5,7 28 e 6,2% 24 e para clindamicina, valores de 2,9 28 e 3,1% 27 . O fato de 16 cepas resistentes à eritromicina serem também resistentes à clindamicina sugere a manifestação do fenótipo MLS B , caracterizado pela resistência constitutiva aos macrolídeos, lincosaminas e estreptogramina B 29,30 . Não houve resistência in vitro ao cloranfenicol, ofloxacina, rifampicina ou vancomicina.…”
Section: Discussionunclassified
“…(5, [16][17][18][19] Despite widespread reports of decreased susceptibility of S. pneumoniae to penicillins, cephelosporins, and macrolides, these remain the most commonly prescribed antibiotics for both children and adults with community acquired pneumonia in the United States and Canada. (4,12) With increasing rates of antibiotic resistance of S. pneumoniae, decisions on treatment of patients with such infections may depend on local antimicrobial susceptibility, as well as clinical outcomes of patients treated with these antibiotics. Prior studies investigating the clinical relevance of antibiotic resistance and mortality in pneumococcal disease have been based on a much smaller number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to concerns about increasing pneumococcal resistance to penicillin, and to provide coverage for atypical pathogens, the American Thoracic Society and Infectious Disease Society of America now recommend considering the use of a macrolide antibiotic plus high dose beta-lactam antibiotic for the empiric outpatient treatment of community acquired pneumonia. (1)(2)(3)(4) Recent surveillance studies of invasive pneumococcal isolates have demonstrated that only 73% of isolates remain susceptible to penicillin, and 78% susceptible to erythromycin. (5) The use of low dosages and long treatment duration with beta-lactam antibiotics have been identified as risk factors for the nasopharyngeal carriage of penicillin resistant organisms.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The rapid increase in resistance among common bacterial pathogens, such as Streptococcus pneumoniae, [3][4][5][6] is widely believed to be fueled by high rates of antibiotic use, much of which is unnecessary. [7][8][9][10][11] Because of the communicability of bacterial pathogens, the consequences of resis-tance have an impact on communities in addition to individual carriers.…”
mentioning
confidence: 99%